2020
DOI: 10.48550/arxiv.2010.03499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Length spectrum compactification of the $\mathrm{SO}_{0}(2,3)$-Hitchin component

Charles Ouyang,
Andrea Tamburelli

Abstract: We find a compactification of the SO0(2, 3)-Hitchin component by studying the degeneration of the induced metric on the unique equivariant maximal surface in the 4-dimensional pseudo-hyperbolic space H 2,2 . In the process, we establish the closure in the space of projectivized geodesic currents of the space of flat metrics induced by holomorphic quartic differentials on a Riemann surface. As an application, we describe the behavior of the entropy of Hitchin representations along rays of quartic differentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In general the map − − → Mix(Σ) → Mix(Σ) has fibers (S 1 ) k where k denotes the number of connected components of Σ ′ . In [DLR10] the set Mix(Σ) is identified with the corresponding set of geodesic currents, a perspective that is generalized in [OT21b,OT20], where the flat metrics associated to cubic (resp. quartic) differentials are considered.…”
Section: We Denote Bymentioning
confidence: 99%
See 2 more Smart Citations
“…In general the map − − → Mix(Σ) → Mix(Σ) has fibers (S 1 ) k where k denotes the number of connected components of Σ ′ . In [DLR10] the set Mix(Σ) is identified with the corresponding set of geodesic currents, a perspective that is generalized in [OT21b,OT20], where the flat metrics associated to cubic (resp. quartic) differentials are considered.…”
Section: We Denote Bymentioning
confidence: 99%
“…A more analytic, and independent approach to compactifications of the space of maximal representations in rank 2 Hermitian Lie groups has been independently pursued by Ouyang [Ouy19], Ouyang-Tamburelli [OT20,OT21a], and Martone-Ouyang-Tamburelli [MOT21]. In their work, they consider the length spectrum of the negatively curved metric induced on the unique invariant minimal surface associated to a maximal representation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Gothen ( [Got01]) showed that there are precisely 3 • 2 2g + 2g − 4 connected components of maximal representations, of which only 2 2g + 2g − 3 are smooth. Of these, 2 2g are isomorphic copies of the Sp(4, R)-Hitchin component, which were analyzed in a previous work ([OT20a]). The remaining 2g − 3 are referred to as Gothen components in the literature and are the main object of study of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper ( [OT20a]), we used this pseudo-Riemannian point of view to define the length spectrum of an Sp(4, R)-Hitchin representation and describe the boundary of this component as projectivized mixed structures, that is hybrid geometric objects on the surface that are measured laminations on some collection of incompressible subsurfaces and flat metrics of finite area induced by meromorphic quartic differentials on the complement. In this note, we show that all Gothen components share the same boundary, precisely Theorem A.…”
Section: Introductionmentioning
confidence: 99%